MODULAR-BLOCK STRUCTURING OF LEARNING MATERIAL IN TRAINING A PROFESSIONAL TEACHER - Kondrashova, L.V. (Pedagogy of Higher and Secondary Education, 2009)
In the possibilities of module-sectional structuring of educational information in the professional becoming of students developing of creative potential of their personality are grounded.